PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA PENYIDIK DITRESKRIMSUS POLDA BALI - Ni Ketut Ledy Sriutami; I Wayan Mendra; Yenny Verawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
With the leadership and competence possessed by each leader and investigator, it will improve the performance of investigators at the Bali Police Ditreskrimsus. This study aims to re-examine the influence of leadership and performance competence of investigators. This research was conducted on investigators of the Bali Police Ditreskrimsus, with a total sample of 53 investigators and located on Jl. W.R. Supratman No. 7 Denpasar. The data analysis technique used is multiple linear regression analysis, multiple correlation analysis, coefficient of determination, F and T test using IBM SPSS Statistics 23.0 for Windows. The results of this study indicate that the leadership variable has a positive and significant effect on investigator performance. As well as the competency variable also has a positive and significant effect on performance. The influence of leadership and competence variables on the investigator performance variable is 88.6% while the remaining 11.4% is influenced by other variables outside of this study.